2004
DOI: 10.1002/marc.200490042
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Rapid Commun. 21/2004

Abstract: Cover: A transmission electron microscope image of microgel particles that consist of welldefined temperature-sensitive poly(N-isopropylacrylamide) cores with pH-sensitive chitosan shells is shown. The microgels are obtained directly from aqueous graft copolymerization of N-isopropylacrylamide and N,N-methylenebisacrylamide from chitosan. The unique coreshell nanostructure exhibits tuneable responses to pH and temperature.Further details can be found in the Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Various types of core-shell microgels have been prepared from the PNIPAAm-grafted polysaccharides. Leung et al [99,100] developed smart microgels that consist of well-defined temperature-sensitive cores with pH-sensitive shells based on PNIPAAm and chitosan. The properties of crosslinked poly(chitosanco-NIPAAm)/poly[methacrylic acid (MAA)-co-methyl methacrylic acid (MMA)] core-shell type copolymer particles were examined [101].…”
Section: Graft Copolymerized Hydrogelsmentioning
confidence: 99%
“…Various types of core-shell microgels have been prepared from the PNIPAAm-grafted polysaccharides. Leung et al [99,100] developed smart microgels that consist of well-defined temperature-sensitive cores with pH-sensitive shells based on PNIPAAm and chitosan. The properties of crosslinked poly(chitosanco-NIPAAm)/poly[methacrylic acid (MAA)-co-methyl methacrylic acid (MMA)] core-shell type copolymer particles were examined [101].…”
Section: Graft Copolymerized Hydrogelsmentioning
confidence: 99%
“…Moreover, the appearance indicates an obvious core-shell nanostructure. This is similar to the reported literature [24]. The polymerization was performed at 70 • C, higher than the LCST of PNIPAM (32 • C).…”
Section: Swelling Behavior and Stability In Alcohol Solutionsmentioning
confidence: 91%
“…Wang et al [21,22] reported the preparation and characterization of PNIPAM/CS hydrogels with semiinterpenetrating and full-interpenetrating polymeric networks. Verestiuc and coworkers [23] described the synthesis of semiinterpenetrating hydrogel by using tetraethyleneglycoldiacrylate as the crosslinker and investigated the controlled release ve- [24] prepared PNIPAM/CS core-shell microgel via a new method, both thermo-sensitivity and pH-sensitivity were characterized. Lin et al [25] reported the synthesis of a multiresponsive coreshell copolymer latex with the crosslinked copolymer of NI-PAM and CS as the core and the copolymer of methacrylic acid and methyl methacrylate as the shell.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of core-shell microgels have been prepared from the PNIPAAm grafted polysaccharides. Leung et al [108,109] developed smart microgels that consist of well-defined temperature-sensitive cores with pH-sensitive shells based on PNIPAAm and chitosan. The unique core-shell nanostructures, which had narrow size distributions, exhibited tunable responses to pH and temperature.…”
Section: Core-shell Type Copolymersmentioning
confidence: 99%